Perception of carbohydrate availability augments high-intensity intermittent exercise capacity under sleep-low, train-low conditions - Waterworth, S. P.; Spencer, C. C.; Porter, A. L.; Morton, J. P. (International Journal of Sport Nutrition and Exercise Metabolism, 2020)
The authors tested the hypothesis that perception of carbohydrate (CHO) availability augments exercise capacity in conditions of reduced CHO availability. Nine males completed a sleep-low train model comprising evening glycogen-depleting cycling followed by an exhaustive cycling protocol the next morning in the fasted state (30 min steady state at 95% lactate threshold followed by 1-min intervals at 80% peak power output until exhaustion). After the evening depletion protocol and prior to sleeping, subjects consumed (a) a known CHO intake of 6 g/kg body mass (TRAIN HIGH) or (b) a perceived comparable CHO intake but 0 g/kg body mass (PERCEPTION) or a known train-low condition of 0 g/kg body mass (TRAIN LOW). The TRAIN HIGH and PERCEPTION trials were conducted double blind. During steady state, average blood glucose and CHO oxidation were significantly higher in TRAIN HIGH (4.01 ± 0.56 mmol/L; 2.17 ± 0.70 g/min) versus both PERCEPTION (3.30 ± 0.57 mmol/L; 1.69 ± 0.64 g/min, p < .05) and TRAIN LOW (3.41 ± 0.74 mmol/L; 1.61 ± 0.59 g/min, p < .05). Exercise capacity was significantly different between all pairwise comparisons (p < .05), where TRAIN LOW (8 ± 8 min) < PERCEPTION (12 ± 6 min) < TRAIN HIGH (22 ± 9 min). Data demonstrate that perception of CHO availability augments high-intensity intermittent exercise capacity under sleep-low, train-low conditions, though this perception does not restore exercise capacity to that of CHO consumption. Such data have methodological implications for future research designs and may also have practical applications for athletes who deliberately practice elements of training in CHO-restricted states.